Pyrolysis of Carbonaceous Particles and Properties of Carbonaceous-g-Poly(acrylic acid) Superabsorbent Polymer for Agricultural Applications - Suriati, Ghazali; Saidatul Shima, Jamari; N., Noordin; K. M., Tan (EDP Sciences, 2016)
Fertilizer and water are very important in determining the production of agriculture nowadays. The excessive use of fertilizer in plantation somehow could leads to environmental pollution. The present study reported a synthesis of controlled release water retention (CRWR) fertilizer coating with superabsorbent polymer (SAPs) that could enhance the utilization of fertilizer and reduce the environmental pollution. In this study, the preparation of carbonaceous-SAPs was carried out via solution polymerization technique by using monomer of poly(acrylic acid) (AA), cross linker, methylene bisacrylamide (MBA) and initiator, ammonium peroxodisulfate (APS) that partially neutralized with sodium hydroxide (NaOH). The CRWR fertilizer was later be prepared by coated the fertilizer granule with carbonaceous-SAPs. The morphology and the bonding formation of the final product of CRWR fertilizer were investigated by using Scanning Electron Microscopy (SEM) and Fourier Transform Infrared Spectrophotometer (FTIR), respectively. Moreover, the water absorbency and water retention in soil were conducted in order to investigate the efficiency of carbonaceous-SAP on the properties of CRWR. Based on the results, the CRWR fertilizer that was coated with carbonaceous-SAP had higher water absorbency value than the CRWR fertilizer without carbonaceous-SAP. 1 wt % CRWR fertilizer in organic soil gave higher water retention ability compared with 1 wt % CRWR fertilizer in top soil. In conclusion, CRWR fertilizer gave a significant influence on the performance of water absorbency and controlled of nutrients release rate as well as function as water retention in soil.